2017
DOI: 10.1016/j.molmed.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cell Differentiation in Chronic Viral Infections: The Tfh Perspective

Abstract: CD4+ T cells play a critical role in the response to chronic viral infections during the acute phase and in the partial containment of infections once chronic infection is established. As infection persists, the virus-specific CD4+ T cell response begins to shift in phenotype. The predominant change described in both mouse and human studies of chronic viral infection is a decrease in detectable Th1 responses. Some Th1 loss is due to decreased proliferative potential and decreased cytokine production in the set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 133 publications
3
63
0
Order By: Relevance
“…Both acute and chronic infection upregulated expression of genes related to the response to CD40 signaling within LZ GC B cells of cluster 4 and along both the branch leading to PC and MBC differentiation as well as the DZ re-entry branch (Figure S5B). This result was consistent with abundant Tfh during both LCMV Arm and clone 13 infections (Crawford et al, 2014;Fahey et al, 2011;Vella et al, 2017) and that CD40 agonism can drive both GC B cell DZ re-entry and terminal PC differentiation in vitro (Erickson et al, 2002;Foy et al, 1996). However, although the enrichment was similar between infections, the pattern of this CD40 help signal was distinct.…”
Section: Chronic Infection Promotes Terminal B Cell Differentiation Asupporting
confidence: 59%
See 2 more Smart Citations
“…Both acute and chronic infection upregulated expression of genes related to the response to CD40 signaling within LZ GC B cells of cluster 4 and along both the branch leading to PC and MBC differentiation as well as the DZ re-entry branch (Figure S5B). This result was consistent with abundant Tfh during both LCMV Arm and clone 13 infections (Crawford et al, 2014;Fahey et al, 2011;Vella et al, 2017) and that CD40 agonism can drive both GC B cell DZ re-entry and terminal PC differentiation in vitro (Erickson et al, 2002;Foy et al, 1996). However, although the enrichment was similar between infections, the pattern of this CD40 help signal was distinct.…”
Section: Chronic Infection Promotes Terminal B Cell Differentiation Asupporting
confidence: 59%
“…Pathway-2 5 level analysis revealed attenuated BCR signaling and increased inflammatory signaling at this decision point that favored GC exit over DZ re-entry. Dysregulation of humoral immunity during chronic infection has been linked to pre-GC B cell deletion (Fallet et al, 2016;Moseman et al, 2016;Sammicheli et al, 2016) and excess Tfh (Crawford et al, 2014;Fahey et al, 2011;Vella et al, 2017), but the B cell intrinsic events in the GC have not previously been defined. The single-cell nature of these studies now identify not only a role for altered GC biology, but also the specific decision point in the GC that is altered by chronic infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulation of PLCs observed in d-HBC patients may explain the occurrence of hypergammaglobulinemia that was one of the hallmarks of CAID and reflects the abnormal systemic inflammation. 24 Our findings suggested that the unbalanced distribution of B cell subsets in patients with cirrhosis may contribute to CAID and play an important role in the progression of the disease. CXCR5 + CD4 + T cell subset is considered as a specialized T cell subset responsible for B cell regulation.…”
Section: Discussionmentioning
confidence: 58%
“…It indicates that the loss of MBs may explain the observed hyporesponsiveness to vaccine in cirrhosis patients. The upregulation of PLCs observed in d‐HBC patients may explain the occurrence of hypergammaglobulinemia that was one of the hallmarks of CAID and reflects the abnormal systemic inflammation . Our findings suggested that the unbalanced distribution of B cell subsets in patients with cirrhosis may contribute to CAID and play an important role in the progression of the disease.…”
Section: Discussionmentioning
confidence: 64%